Multiple clusters of A(H1N1)pdm09 virus circulating in severe cases of influenza during the 2010–2011 season: A phylogenetic and molecular analysis of the neuraminidase gene. Issue 6 (12th April 2013) - Piralla, Antonio; Pariani, Elena; Campanini, Giulia; Rovida, Francesca; Ranghiero, Alberto; Fiorina, Loretta; Amendola, Antonella; Zanetti, Alessandro; Baldanti, Fausto
Abstract: The molecular characterization of circulating influenza A viruses is crucial to detect mutations potentially involved in increased virulence, drug resistance and immune escape. A molecular and phylogenetic analysis of A(H1N1)pdm09 neuraminidase (NA) gene sequences from different patient categories defined according to the severity of influenza infection were analyzed. A total of 126 influenza A(H1N1)pdm09 positive samples from patients with severe infections in comparison with those with moderate and mild infections was performed in Lombardy (Northern Italy, nearly 10 million inhabitants) during the 2010–2011 season. NA sequences included in this study segregated into five distinct clusters. Nineteen amino acid substitutions were detected exclusively in NA sequences of viruses identified in patients with severe or moderate influenza infection. Three of them (F74S, S79P, E287K) were observed in virus strains with the 222G/N hemagglutinin mutation. None of NA sequences under study had mutations related to the resistance to the NA inhibitors. Four out of 126 (3.2%) NA sequences from patients with severe infection lost a N‐linked glycosylation site due to the change from N to K at residue 386. Two additional N‐linked glycosylation sites in the NA stalk region (residues 42 and 44) were found in 12 (9.5%) NA sequences. Sporadic NA mutations were detected in NA viral sequences from critically ill patients, and no variants with reduced sensitivity to NA inhibitors were observed either in treated or untreated patients. J. Med. Virol. 85: 944–952, 2013. © 2013 Wiley Periodicals, Inc.